2014
DOI: 10.7125/apan.38.14
|View full text |Cite
|
Sign up to set email alerts
|

Design and Development of a Remote Station for Real-time Monitoring of Urban Flooding

Abstract: This paper presents the design and development of urban flood monitoring stations that use pressure sensor to determine flooding levels. GPRS and SMS were used to communicate data from the remote stations to a server located at a data center. A web-based visualization tool has been developed to allow access to data in real-time. Based on experiments, the sensor measurements have a difference of 0.872cm to 3.067cm with actual values. The higher differences tend to be associated with higher water levels while lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…According to the recent surveys on mobile GIS, it was found that most flood monitoring systems primarily utilized sensed hydrological and meteorological data, such as rainfalls and runoffs, etc. (Sunkpho, and Ootamakorn 2011;Ancona et al 2014;Retamar et al 2014;Pagatpat et al 2015;Chen et al 2018). Information was presented on various smart device platforms, running web or native application (Sunkpho and Ootamakorn 2011;Ancona et al 2014) or as descriptive text via short message service (SMS) (Retamar et al 2014).…”
Section: Internetworking Mobile Gis For Flood Monitoring and Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the recent surveys on mobile GIS, it was found that most flood monitoring systems primarily utilized sensed hydrological and meteorological data, such as rainfalls and runoffs, etc. (Sunkpho, and Ootamakorn 2011;Ancona et al 2014;Retamar et al 2014;Pagatpat et al 2015;Chen et al 2018). Information was presented on various smart device platforms, running web or native application (Sunkpho and Ootamakorn 2011;Ancona et al 2014) or as descriptive text via short message service (SMS) (Retamar et al 2014).…”
Section: Internetworking Mobile Gis For Flood Monitoring and Managementmentioning
confidence: 99%
“…(Sunkpho, and Ootamakorn 2011;Ancona et al 2014;Retamar et al 2014;Pagatpat et al 2015;Chen et al 2018). Information was presented on various smart device platforms, running web or native application (Sunkpho and Ootamakorn 2011;Ancona et al 2014) or as descriptive text via short message service (SMS) (Retamar et al 2014). Common information included areaspecific water level, whose current status could be observed in real-time.…”
Section: Internetworking Mobile Gis For Flood Monitoring and Managementmentioning
confidence: 99%
“…[2] In view of this, the Department of Science and Technology -Advanced Science and Technology Institute (DOST-ASTI) is implementing a project entitled "Flood sensor Development, Installation, and Monitoring of Urban Flooding in Metro Manila", which aims to develop and implement 60 urban flood stations along with a software solution for monitoring street-level flooding in real time at predetermined levels. [3] In our previous paper [3], we discussed the design and prototype development of a remote monitoring station for the monitoring of urban flooding, however, the previous study lacks data gathering during heavy rain conditions and several features from the visualization tool, namely a historical data archive and a mobile application in order to deliver updates for users on the road. It was also noted that the 3-10 minutes sending interval of the data logger is a considerable lag time for the getting the next flood readings.…”
Section: Introductionmentioning
confidence: 99%